PENGARUH ABNORMAL RETURN dan TRADING VOLUME ACTIVITY TERHADAP HARGA SAHAM - Ananda, Cindy (COMPETITIVE, 2021)
The purpose of this study is to determine 1) the effect of abnormal return on stock price, 2) the effect of trading volume activity on stock price, 3) the effect between abnormal return and trading volume activity on stock prices. The variable in this study is the stock price, abnormal return, and trading volume activity. The method in this study is to use the quantitative.  Population method used in this study. The research is a trading sector company listed on the Indonesia Stock Exchange and the sample used is 19 trading companies which are determined by purposive sampling. The data collection technique used in this study is to use secondary data and documentation. Based on the result research that has been carried out, it produces 1) simultaneously abnormal return and trading volume activity have a effect on stock price, 2) partially abnormal return has no effect on stock price, 3) trading volume activity partially has a effect the stock price of trading sector companies listed on the indonesia stock exchange period 2015-2019.